The Impact of the Digital Revolution on Strategic Management Thinking: An SLR Study - Surnantaka, I Wayan (Journal of Advances in Accounting, Economics, and Management, 2025)
The digital revolution is reshaping the business landscape, significantly influencing how companies operate through advances in digitization and e-commerce. This transformation impacts not only operational efficiency but also organizational culture, requiring new mindsets and work processes. This study explores the effects of digital transformation on strategic management theory and practice, addressing how it has influenced the evolution of strategic management, shifted the concept of competitive advantage, and moved business strategies from traditional to digital approaches. Using a Systematic Literature Review (SLR) method, the research analyzes existing studies to understand the impact of digitalization on strategic management. The findings reveal that digitalization has led to a shift from classical strategies based on market position and resource advantages to more dynamic, technology-driven models. Competitive advantage now depends on innovation, technology adoption, and data-driven decision-making. Additionally, organizations must adapt by integrating traditional and digital strategies, fostering a digital culture, and enhancing flexibility to maintain competitiveness in the digital era.